Doubt in the Legal Capacity of Smart Contract’s Parties and the Possibility of Applying the Principle of Correctness in the Assumption of Non-Qualification - Mohammad Hasan Taj Langerudi; Farzin Dehdar (پژوهشهای حقوقی)
As one of the relatively new topics of the technology world, the smart contract has different angles and dimensions in the field of conclusion and execution, which must be analyzed from a legal perspective. This contract is implemented on the platform of software such as Ethereum and has features that blockchain technology benefits from. The smart contract is concluded and executed without the parties' capacities being verified, and this is considered one of its most important legal challenges in the conclusion stage. In the forward research, it is tried to introduce the mentioned feature in detail, and after providing solutions to solve this legal defect and verifying the eligibility of the parties, the criticisms of it will be expressed and it will be explained that the anonymity of the parties as one of the certain features of the smart contract should be recognized. Then this matter is subject to jurisprudential and legal scrutiny, whether it is possible to invoke the principle of correctness despite the lack of competence of the parties in the smart contract, or whether this transaction should be considered invalid.